WIEDZA I DEKLAROWANE POSTAWY RODZICÓW WOBEC SZCZEPIEŃ OCHRONNYCH DLA DZIECI W WARSZAWIE I TALLINIE - Klotško, Małgorzata; Walewska-Zielecka, Bożena; Olejniczak, Dominik; Skonieczna, Joanna (Journal of Education, Health and Sport, 2015)
Klotško Małgorzata, Walewska-Zielecka Bożena, Olejniczak Dominik, Skonieczna Joanna. Wiedza i deklarowane postawy rodziców wobec szczepień ochronnych dla dzieci w Warszawie i Tallinie = Knowledge and declared attitude of parents to protective vaccination for children in Warsaw and Tallin. Journal of Education, Health and Sport. 2015;5(12):89-98. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35011 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A89-98 http://pbn.nauka.gov.pl/works/676933 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.09.2015. Revised 25.10.2015. Accepted: 08.12.2015. WIEDZA I DEKLAROWANE POSTAWY RODZICÓW WOBEC SZCZEPIEŃ OCHRONNYCH DLA DZIECI W WARSZAWIE I TALLINIE KNOWLEDGE AND DECLARED ATTITUDE OF PARENTS TO PROTECTIVE VACCINATION FOR CHILDREN IN WARSAW AND TALLIN Małgorzata Klotško1, Bożena Walewska-Zielecka2, Dominik Olejniczak2, Joanna Skonieczna2 1 Absolwentka kierunku Zdrowie Publiczne Wydział Nauki o Zdrowiu Warszawski Uniwersytet Medyczny 2 Warszawski Uniwersytet Medyczny Zakład Zdrowia Publicznego ul. Banacha 1a, 02-097 Warszawa Adres do korespondencji: dr hab. n. med. Bożena Walewska- Zielecka Warszawski Uniwersytet Medyczny Zakład Zdrowia Publicznego ul. Banacha 1a, 02-097 Warszawa Tel: 22 599 21 80 Fax: 22 599 21 81 Słowa kluczowe: szczepienia ochronne, zachowania zdrowotne, Polska, Estonia. Keywords: vaccination, health behaviors, Poland, Estonia. Streszczenie Wprowadzenie Szczepienia, jako jedno ze szczytowych osiągnięć w medycynie stanowią istotny element realizowania polityki zdrowotnej na szczeblu krajowym I globalnym. Regularne uodparnianie dzieci oraz ludzi dorosłych poprawiło jakość i przedłużyło długość życia. Ponadto szczepienia wyeliminowały ospę prawdziwą oraz przyczyniły się do ograniczenia występowania niektórych chorób takich jak polio, świnki czy tężca. Szczepienia zaliczane są do profilaktyki swoistej pierwszego rzędu, która ma za zadanie wpływać na jeden z trzech elementów łańcucha epidemicznego - na wrażliwą populację. Materiał i metody Materiał stanowiło 231 osób rodziców dzieci objętych obowiązkowymi szczepieniami ochronnymi w Warszawie i Tallinie. Wśród ankietowanych znalazły się 173 oraz 58 mężczyzn.. Badanie było przeprowadzone przy użyciu komputera CAWI (ang. Computer-Assisted Web Interview) oraz metodą papierową PAPI (ang. Paper nad Pencil Interview). Do obliczeń korelacji zastosowano test Chi, zaś za poziom istotności przyjęto wartość 0,05. Wyniki Po zastosowaniu metody top2boxes wynika, że w Estonii 30% wierzy w bezpieczeństwo szczepionek, natomiast 70% nie. W Polsce wynik ten kształtuje się odpowiednio na poziomie 38% i 62%. Po zastosowaniu metody top2boxes wynika, że w Estonii 48% badanych widzi w pormowaniu szczepień interes producentów, natomiast 52% nie zgadza się z tym. Natomiast w Polsce na korzyści koncernów wskazuje 59% i 41 % zaprzecza tej teorii. Po zastosowaniu metody top2boxes okazuje się, że w Estonii 84% badanych popiera dobrowolność szczepień, natomiast 15% jest przeciwnych. Natomiast w Polsce jest 65% zwolenników dobrowolności szczepień i 35 % jej przeciwników. Wnioski Rodzice w Estonii i Polsce są świadomi zalet wypływających ze szczepienia dzieci. Może świadczyć o tym udzielenie przez większość ankietowanych pozytywnych odpowiedzi na pytanie 1,2 i 3. Niestety większość z nich nie posiada wiedzy na temat największego osiągnięcia szczepień jakim jest eradykacja ospy prawdziwej w 1980 roku. Może to świadczyć o braku informacji na ten temat ze strony instytucji zajmujących się ochroną zdrowia jak i samego personelu medycznego, szczególnie lekarzy rodzinnych. Rodzice dzieci w Polsce i Estonii nie są wystarczająco informowani na temat wpływu szczepień na zdrowie dziecka. Świadczy o tym zaznaczenie przez większość respondentów pozytywnych odpowiedzi na pytanie 4, 5, i 6. W celu poprawy tej sytuacji należy edukować społeczeństwo poprzez rzetelne kampanie społeczne. Bardzo dużą role powinien odgrywać tutaj personel medyczny, a szczególnie położne, lekarze rodzinni i pediatrzy. Abstract Introduction. Vaccination as one of the top achievements in medicine is an important part of implementing health policy at the national and global levels. Regular immunization of children and adults improved quality of life and extended its expectancy. In addition, inoculation eliminated smallpox and have contributed to reducing the incidence of certain diseases such as polio, mumps and tetanus. Vaccination is classified as specific first order prevention which affects one of the three components of an epidemic chain - the sensitive population. Material and methods The material consisted of 231 persons (parents of children) covered by the mandatory vaccinations in Warsaw and in Tallinn (Estonia). Among those surveyed were 173 and 58 men. The study was conducted using a computer CAWI (Computer-Assisted Web Interview) approach and paper PAPI (Paper on Pencil Interview) one. For the calculation of correlation a Chi test was used, and a level of significance was set at 0.05. Results After applying the top2boxes method following results appeared. In Tallinn 30% of respondents believe in the safety of vaccines, while 70% do not. In Warsaw, these results are respectively 38% and 62%. When it comes to promoting of vaccination there are 48% of respondents in Estonia who see the interest of vaccine producers in its promoting, while 52% of them disagree with that. Whereas in Poland 59% of them are for the benefit of corporations and 41% deny this theory. Differences are seen in regard of the voluntary vaccination. It appears that in Estonia there are 84% of respondents who support its voluntariness, while 15% are opposed. In Poland it is 65% as proponents of vaccination voluntariness and 35% as opponents of it. Conclusions Parents in Estonia and Poland are aware of the advantages arising from the vaccination of children. It may indicates from positive responses to the initial three questions of the majority of respondents. Unfortunately most of them do not have knowledge about the greatest achievement of vaccination which is the eradication of smallpox in 1980. This may indicate a lack of information from the institutions dealing with the health care and the medical staff, especially family doctors. Parents of children in both countries are not sufficiently informed about the impact of vaccination on the health of the child. Evidence of this is selection of positive answers to following three questions by the majority of respondents. In order to improve this situation should educate the public should be educated by reliable social campaigns. A very big role here should be played by medical personnel, particularly midwives, family doctors and pediatricians.